Faktor yang Berpengaruh terhadap Emisi Karbon dalam Kerangka Pembangunan Berkelanjutan: Analisis Empiris di Indonesia - Astia Saputri; Deky Aji Suseno (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2025)
Carbon dioxide (CO₂) emissions are one of the main causes of climate change in the world. This study aims to analyze the impact of urbanization on carbon emissions within the framework of sustainable development, taking into account mediating variables such as gross domestic product (GDP) per capita, fossil energy consumption, renewable energy consumption, and forest cover area. The method used is a quantitative approach employing Structural Equation Modeling–Partial Least Squares (SEM-PLS) using WarpPLS 8.0. Data sources include Our World in Data and the World Bank, covering the period from 1990 to 2022. The results show that urbanization has a significant positive impact on GDP per capita and fossil fuel consumption with coefficients of 0.99 and 0.98. Urbanization also has a significant negative impact on renewable energy consumption and forest cover area with coefficients of -0.99 and -0.99. GDP per capita and fossil fuel consumption have a significant positive impact on carbon emissions, with coefficients of 0.33 and 0.47. Renewable energy consumption and forest cover area each show a significant negative impact on carbon emissions, with coefficients of -0.38 and -0.41. However, the direct relationship between urbanization and carbon emissions shows a non-significant positive effect with a coefficient of 0.24. These findings conclude that urbanization in Indonesia contributes to an increase in carbon emissions indirectly through mediating variables, while its direct relationship with emissions is not significant.